Documentation, structural health monitoring and numerical modelling for damage assessment of the Morris Island Lighthouse. (7th October 2019) - Blyth, Anna; Napolitano, Rebecca; Glisic, Branko
Abstract : Heritage structures serve as invaluable records of cultural achievement that should be preserved for future generations. To ensure the successful preservation of these structures, there must be an affordable and effective way to conduct conservation. The objective of this work is to outline an efficient workflow for the structural analysis of preservation projects through a case study on the Morris Island Lighthouse in Charleston, South Carolina. Thorough documentation of the cultural significance and structural condition of the lighthouse was completed through archival research, photogrammetry and crack mapping. Structural Health Monitoring and Distinct Element Modelling were used to analyse past structural damage and the present condition. The behaviour of masonry and crack propagation was evaluated under gravity, wind, wave and seismic loading. The results of these analyses were summarized in a virtual tour and informational modelling environment, which allows the results to be accessed and associated with their physical location on the structure. The benefits and limitations of this process are discussed, and a standardized workflow for efficient structural analysis of cultural heritage is proposed. This article is part of the theme issue 'Environmental loading of heritage structures'.